Effect of hierarchical precipitates on corrosion behavior of fine-grain magnesium-gadolinium-silver alloy. (January 2022) - Xu, Bingqian; Sun, Jiapeng; Han, Jing; Yang, Zhenquan; Zhou, Hao; Xiao, Lirong; Xu, Songsong; Han, Ying; Ma, Aibin; Wu, Guosong
Abstract: An equal channel angular pressing (ECAP) process is used to obtain a fine-grain magnesium-gadolinium-silver alloy, and hierarchical precipitates embedded in the fine-grain matrix are achieved by subsequent peak-aging. These hierarchical precipitates are composed of the β phase sub-microparticles, β phase nanoparticles, γ" phase nanoplates, and β' phase nanoplates. They facilitate corrosion in the 3.5 wt% NaCl solution to some extent due to micro-galvanic corrosion. However, compared to those precipitates in the as-cast alloy, the spatial redistribution of the hierarchical precipitates improves the corrosion resistance of the material, which is possibly attributed to the formation of a protective corrosion product film. Highlights: Peak-aging following equal channel angular pressing is conducted on Mg-Gd-Ag alloy. Hierarchical precipitates are successfully achieved in fine-grain Mg-Gd-Ag alloy. Its corrosion rate may be controlled by hierarchical precipitates.